The Role of Trust in Mediating the Effects of Perceived Usefulness and Perceived Ease of Use on Customer Loyalty among QRIS Users in Denpasar - I Gusti Bagus Krisna Saputra; I Gusti Ayu Ketut Giantari; Ni Wayan Ekawati; I Gusti Ngurah Jaya Agung Widagda (Indonesian Journal of Business Analytics, 2026)
The purpose of this study is to examine how trust influences customer loyalty among Denpasar City QRIS users in relation to perceived usefulness and perceived ease of use. The study used a quantitative methodology, and 120 QRIS users who were chosen by purposive sampling were given questionnaires to complete. Partial Least Squares Structural Equation Modelling (PLS-SEM) was used to analyse the data in order to look at direct and mediating correlations between variables. The results show that customer loyalty is positively and significantly impacted by perceived usefulness, but not by perceived simplicity of use. Customer loyalty is greatly impacted by trust, which is heavily influenced by perceived utility and perceived simplicity of use. Additionally, mediation analysis reveals that trust fully mediates the association between perceived ease of use and customer loyalty and somewhat mediates the relationship between perceived usefulness and customer loyalty.